2022
DOI: 10.1186/s12936-022-04401-5
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and use of long-lasting insecticidal nets three months after a mass distribution campaign in Uganda, 2021

Abstract: Background Uganda conducted its third mass long-lasting insecticidal net (LLIN) distribution campaign in 2021. The target of the campaign was to ensure that 100% of households own at least one LLIN per two persons and to achieve 85% use of distributed LLINs. LLIN ownership, use and associated factors were assessed 3 months after the campaign. Methods A cross-sectional household survey was conducted in 14 districts from 13 to 30 April, 2021. Househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The campaign’s objective was thus met despite the difficulties caused by COVID-19-related disruptions. The campaign’s coverage is consistent with a study conducted in 14 districts three months after the 2020/2021 campaign, which found that nearly all (96%) surveyed households owned at least one LLIN [ 24 ]. Another study conducted 1–5 months after distribution in 12 districts found that more than 93% of households had at least one LLIN obtained through the 2020/2021 campaign [ 17 ].…”
Section: Discussionsupporting
confidence: 85%
“…The campaign’s objective was thus met despite the difficulties caused by COVID-19-related disruptions. The campaign’s coverage is consistent with a study conducted in 14 districts three months after the 2020/2021 campaign, which found that nearly all (96%) surveyed households owned at least one LLIN [ 24 ]. Another study conducted 1–5 months after distribution in 12 districts found that more than 93% of households had at least one LLIN obtained through the 2020/2021 campaign [ 17 ].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, factors such as educational status of the mother of the household and the problems related to LLINs use such as discomfort due to heat and lack of airflow under LLINs were reported by the households to affect their LLINs usage. Similar observations from Tanzania, and Uganda have recognized that low use of bed nets in the tropical areas is related to the heat discomfort due to poor airflow caused by the bed nets ( 39 , 40 ). As a protective tool, LLINs are the most effective instruments for protection against mosquito bites and malaria transmission ( 41 ).…”
Section: Discussionmentioning
confidence: 60%
“…In 2022, 44 countries planned such campaigns to distribute 241 million LLINs, which required spending very significant logistical and financial efforts [19]. While MDCs help improve ownership, population access and use of nets immediately after distribution [2,20,21,22,23,24,25], these endeavours often deteriorate into inefficient systems with nets unevenly distributed amongst households [6]. Furthermore, LLIN indicators frequently drop steeply relatively soon after distribution compromising use, as observed on Bioko [26,27].…”
Section: Discussionmentioning
confidence: 99%